Study of Phenotypic and Molecular Approaches of Potyvirus plumpoxi Resistance Evaluation in New Czech Apricot Hybrids - Eliška Zezulová; Tomáš Kiss; Kateřina Baránková; Tomáš Nečas (HortScience)
This study investigates the resistance of 17 apricot hybrids to Potyvirus plumpoxi (PPV) with the use of phenotyping, serological assays [double-antibody-sandwich enzyme-linked immunosorbent assay (DAS-ELISA)], and molecular marker analyses. The expression of symptoms expression was evaluated on four occasions throughout the course of the experiment, while the presence of the virus in the plant was diagnosed by DAS-ELISA. In addition, the genotyping with simple sequence repeat (SSR) markers (PGS1.21, PGS1.23) and ParPMC2 allele-specific polymerase chain reaction (PCR) for the purpose of evaluating PPV resistance. A total of five new apricot hybrids were evaluated as resistant to PPV, while five hybrids exhibited resistance despite the presence of some PPV symptoms. In addition, three hybrids demonstrated genotype-phenotype incongruences (GPIs). The statistical analysis revealed a significant relation between PPV-positive plants and the absence of resistance-associated alleles, confirming that allelic composition is strongly associated with phenotypic resistance. The average value of symptoms evaluation was 0.3 ± 0.1 for resistant hybrids and 1.7 ± 0.3 and 1.5 ± 0.4 for susceptible hybrids evaluated by PGS1.21 and PGS1.23, respectively. The Tukey’s honestly significant difference (HSD) test showed the significant difference between genotypes evaluated by ParPMC2 marker as “RR” and “RS” (resistant) from “SS” (susceptible). However, discrepancies in hybrid resistance evaluation highlight the complexity of inheritance and the potential errors in genotyping. These results indicate that the most reliable method for evaluating PPV resistance is the time-consuming phenotyping method. Conversely, the use of SSR markers greatly improves the effectiveness of breeding